Access to and benefit-sharing of marine genetic resources beyond national jurisdiction: Developing a new legally binding instrument - Carlos María Correa (South Centre, 2017)
This paper examines the underlying principles and main elements of binding and non-binding international instruments relating to access and benefit-sharing of genetic resources. It discusses the gap left by the United Nations Convention on the Law of the Sea and some of the elements that might be considered in developing a new legally-binding instrument on access and benefit-sharing derived from the exploitation of marine genetic resources found in areas beyond national jurisdiction, as mandated by the United Nations General Assembly. The paper further elaborates on some of the problems faced in the implementation of the Convention on Biological Diversity and other international instruments on genetic resources and the extent to which the principles and operative mechanisms of those instruments may provide guidance for the development and adoption of that new instrument.
Keywords: 300; Artenvielfalt; Immaterialgüterrechte; Ressourcennutzung; Seerecht; Internationales Recht; Welt